THE EFFECT OF TRUST AND SERVICE QUALITY ON BSI MOBILE BANKING USER SATISFACTION WITH CUSTOMER LOYALTY AS AN INTERVENING VARIABLE (CASE STUDY OF IAIN KUDUS STUDENTS) - JABBAR, MUHAMMAD QISMATAL; HANA, KHARIS FADLULLAH (Institut Agama Islam Negeri (IAIN) Bone, 2025)
This study aims to analyze the influence of trust and service quality on the loyalty of BSI Mobile Banking users, with customer satisfaction as an intervening variable. The study was conducted on IAIN Kudus students as active users of BSI Mobile. The associative quantitative method was used in this study, with data analysis techniques using Structural Equation Modeling (SEM) based on Partial Least Square (PLS) through SmartPLS software. The results showed that trust had a significant effect on loyalty, while service quality did not have a significant effect. Customer satisfaction as an intervening variable also did not have a significant effect on user loyalty. This study provides new insights for the development of mobile banking applications based on trust and quality service in the context of Islamic banking.